2010
DOI: 10.1038/aps.2010.117
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidins in inflammation and tissue repair: Potential therapeutic applications for gastrointestinal disorders

Abstract: Cathelicidins, a family of host defense peptides, are highly expressed during infection, inflammation and wound healing. These peptides not only have broad-spectrum antimicrobial activities, but also modulate inflammation by altering cytokine response and chemoattraction of inflammatory cells in diseased tissues. In this connection, a mouse cathelicidin has been demonstrated to prevent inflammation in the colon through enhancing mucus production and reducing production of pro-inflammatory cytokines. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 43 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…Cathelicidins can influence chemoattraction and cytokine release from cells of the immune system [110,138,139]. LL-37 is a chemoattractant for neutrophils, monocytes, dendritic and T-cells [72,140,141].…”
Section: Ll-37 and Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathelicidins can influence chemoattraction and cytokine release from cells of the immune system [110,138,139]. LL-37 is a chemoattractant for neutrophils, monocytes, dendritic and T-cells [72,140,141].…”
Section: Ll-37 and Immune Systemmentioning
confidence: 99%
“…Epithelial cells IL-6 [153] Human gingival fibroblasts IL-6 [154] Keratinocytes IL-1b [138], IL-6 [23,155] Macrophagelike cell lines TNF-a [156] Mast cells Histamine, IL-2, IL4, IL-6 [157] Mesenchymal stromal stem cells CCL5, IL-6, IL-10, IL-12, MMP-2, TNF-a, VEGF [39,151] Monocytes/macrophages CCL3, IL-1b, IL10, IL18 [151,156,158] NIH 3T3 fibroblast cells IL-1b [159] Microglia and astrocytes CCL-2, IL-1b, IL-6, IL-8 [160] CCL: chemokine (C-C motif) ligand, IL: interleukin, MMP: matrix metalloproteinase, TNF: tumor necrosis factor, VEGF: vascular endothelial growth factor. observed that during an infection, LL-37 suppressed epithelial cell apoptosis in intestinal epithelium and skin, respectively [187,188].…”
Section: Cellsmentioning
confidence: 99%
“…LL-37 is the only cathelicidin-derived peptide found in humans (LL-37-hCAP18) (44, 216218). LL-37-hCAP18 is expressed in epythelia, monocytes, and lymphocytes.…”
Section: Nmr Spectroscopic Approaches To Study Ampsmentioning
confidence: 99%
“…Cathelicidins comprise a group of host-defense peptides, which are highly expressed during infection, inflammation, and wound healing (Wu et al, 2010). The only human cathelicidin LL37 was found to be expressed in superficial epithelial, parietal, and chief cells in fundic glands of the normal gastric mucosa (Hase et al, 2003).…”
Section: Introductionmentioning
confidence: 99%